ANALISIS DAYA TARIK FESTIVAL BERBASIS MASYARAKAT SEBAGAI PRODUK WISATA BUDAYA DI PULAU KARIMUNJAWA - Atika Nur Hidayah; Kurnia Fahmy Ilmawan; Andreas Yogi Prasetyo (Jurnal Paradigma Multidisipliner (JPM), 2022)
Community-based festival is considered as a catalyst for developing sustainable tourism in the destination. Hence, it is necessary to conduct a study on the attracvtiveness of the community-based festival as a tourism product in a destination. This study explores and analyse the attractiveness of Festival Barikan Kubro as a community-based festival in Karimunjawa Island through several aspects, namely, aesthetic, uniqueness, spirituality, and science aspect. This study is a qualitative case study using ethnographic approach employing participant observation and in-depth interviews to gain a deep understanding on the management of the festival. The triangulation technique is used by comparing the observations, interviews, and documentation of the festival. The data were then thematically coded based on the dimension of festival attarctiveness. The result of this study showed that the community-based festival attractiveness includes historical values, socio-cultural values locality, spirituality, environmental conservation and cultural educational values. In conclusion, community-based festival as a tourism product diversifies the tourism attraction in Karimunjawa and contributes to the development of sustainable ecotourism in Karimunjawa Island.Keywords: festival attractiveness, cultural tourism, community-based festival.